(untitled) (Student’s Journal of Health Research Africa, 2024)
Background The study aimed to assess the Medical Records Management System (MRMS) in the Management of Tuberculosis Patients at St. Francis Nsambya Hospital. Methodology A cross-sectional design was used to assess the current state of the MRMS, including its structure, utilization, and functionality at a single point in time. The study targets the staff in the TB clinic who use the existing medical records management systems to manage TB patients. Participants were sampled using a non-probability method, specifically purposive sampling. The study encompassed qualitative data collection from home care section, where the TB clinic is found, including a target study population, face-to-face interviews, document review guide, and observation guides. Result The study had a total of 12 participants but only 9 responded. The majority of which were record program administrators (75%) & had 2-2.9 years of experience in using the medical records. Pertaining to the status of TB records many (83.3%) said that TB records were in an active state, while the rest reported they were in both active and semiactive states. All respondents (100%) confirmed the use of a centralized system. Identified challenges in filing and storage of TB records were: Misfiling and misplacement of records (100%), Delayed retrieval of records (100%), Overcrowding of files on shelves (66.7%), Lack of sufficient staff with expertise in records filing and storage (50%) and inadequate storage equipment (50%). Conclusion The back-to-front filing method used in the hospital, ensured the strategic placement of new documents on top of preceding ones, simplifying document retrieval. The findings highlighted the hospital’s commitment to systematic filing practices, furthermore the hospital’s dedication to maintaining accessible records for current healthcare activities. Moreover, the need for targeted interventions to enhance records management practices. Recommendations Methods towards filing and storage need to be improved, challenges addressed, and enhancement in record management